JogjaKita Application: Efforts to Revitalize DIY MSMEs in Forming the Digital Economy Through Collaboration between the Government and Entrepreneurs in the Digital Era - Widyasari, Sindy; Kurniawan, Akhmad; Azzahra, Fadia; Solihah, Sayidah Ummul; Iskandar, Ghazian Avryllio; Darumurti, Awang (Universitas Muhammadiyah Ponorogo, 2024)
It is recorded that around 80% of DIY MSMEs have no right platform to market their products digitally. DIY MSMEs still lack in terms of innovation and the desire to improve quality through digital. Through the Provincial Cooperative & SME Service, the DIY government collaborates with PT JogjaKita Multi Andalan to deal with these problems. Therefore, this research aims to discover the collaboration model between the DIY Government and entrepreneurs through the JogjaKita application in the revitalization of digital-based MSMEs in the digital era 4.0. This research used a qualitative method with a case study approach and analyzed using an interactive model assisted by Nvivo 12 Plus. The research results show that the established collaboration is relatively successful. The collaboration model begins with a face-to-face dialog, and then building trust which takes a long time, around two years due to an internal conflict within the JogjaKita Company. This collaboration is quite helpful for several MSMEs in increasing the capacity and sales transactions. However, some obstacles still need to be faced, such as the small number of MSME actors who use the SiBakul free shipping service on the JogjaKita application, as well as the uneven distribution of infrastructure network in DIY.